2014
DOI: 10.1063/1.4895924
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism of zigzag edge phosphorene nanoribbons

Abstract: We have investigated, by means of ab initio calculations, the electronic and magnetic structures of zigzag edge phosphorene nanoribbons (ZPNRs) with various widths. The stable magnetic state was found in pristine ZPNRs by allowing the systems to be spin-polarized. The ground state of pristine ZPNRs prefers ferromagnetic order in the same edge but antiferromagnetic order between two opposite edges. The magnetism arises from the dangling bond states as well as edge localized π-orbital states. The presence of a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
92
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 21 publications
11
92
1
1
Order By: Relevance
“…5(b)], while the 4-ZPNR-H has a ferromagnetic one [see Fig. 5(d)], in consistent with the previous magnetic analysis for the ZPNRs 36 . The band structures of the source and the drain give nearly symmetric spin-dependent transmission spectra as shown in Fig.…”
Section: Fig 3 (Color Online) (A)-(d) the Total Spin Current Is Andsupporting
confidence: 78%
“…5(b)], while the 4-ZPNR-H has a ferromagnetic one [see Fig. 5(d)], in consistent with the previous magnetic analysis for the ZPNRs 36 . The band structures of the source and the drain give nearly symmetric spin-dependent transmission spectra as shown in Fig.…”
Section: Fig 3 (Color Online) (A)-(d) the Total Spin Current Is Andsupporting
confidence: 78%
“…In contrast, all bare zPNRs are metallic regardless of the ribbon width . Zhu et al further demonstrated that the dangling band states in bare zPNRs are ferromagnetically coupled in one edge but antiferromagnetically coupled between two edges . However, both aPNRs and zPNRs become semiconducting with a direct band gap after hydrogen termination …”
Section: Property Tuningmentioning
confidence: 99%
“…Indeed, the edge magnetism of black phosphorene nanoribbon was strongly affected by the edge relaxation effect. 24 For instance, the pristine black phosphorene layer with an ideal structure had magnetic moments at the edge atoms, but the magnetic states vanished after structure relaxation. Thus, we first examined the edge magnetism of ZBPNRs affected by the structure relaxation.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the magnetic state appeared at the edge atoms in an ideal nanoribbon structure, but the edge magnetism vanished after the structure relaxation. 24,25 Thus, all the black phosphorene nanoribbons do not show spin polarized state. As compared with the black phosphorene, the blue phosphorene 26 has a different characteristic in the structural point of view.…”
mentioning
confidence: 96%